2022
DOI: 10.1055/a-1899-8862
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium, Magnesium, and Phosphorus Levels in Patients with COVID-19: Relationships with Poor Outcome and Mortality

Abstract: In this retrospective study to assess the impact of serum corrected calcium (CorrCa), magnesium (Mg) and phosphorus (P) levels, all adult patients with laboratory-confirmed COVID-19 hospitalized during 2020 were included. Poor outcome was considered in patients who presented need for mechanical ventilation, intensive care unit (ICU) admission, or in-hospital mortality. We analyzed 2473 patients (956 females) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Notably, this association persisted even after adjustment for significant confounding factors [30]. But not all studies demonstrated the predictive value of lower ionized calcium levels for a worse prognosis [25,[31][32][33]. It is possible that perturbations in the ionized calcium values in acutely ill patients represent an adaptive and protective response, and some data suggest that calcium administration may be harmful in critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this association persisted even after adjustment for significant confounding factors [30]. But not all studies demonstrated the predictive value of lower ionized calcium levels for a worse prognosis [25,[31][32][33]. It is possible that perturbations in the ionized calcium values in acutely ill patients represent an adaptive and protective response, and some data suggest that calcium administration may be harmful in critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that patients with viral infections are at a high risk of developing hypocalcemia, 45 which is a risk factor for hospitalization 46 . Although COVID‐19 pneumonia presents primarily as a respiratory system disease, it may worsen or lead to cardiac events or dysfunction of other organs, including the liver and kidneys, with increasing severity, according to its clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a retrospective cohort study revealed that low serum Mg levels are negatively associated with myocardial damage in patients with COVID-19 [70]. In addition, Mg deficiency may affect bronchial smooth muscle relaxation, causing respiratory dysfunction [71], which can lead to the need for mechanical ventilation, ICU admission, and poor outcomes among patients with COVID-19 [72]. A recent study of patients admitted to the ICU indicated that hypomagnesemia was independently associated with COVID-19 severity (high Acute Physiology and Chronic Health Evaluation [APACHE] score and lung involvement) [55].…”
Section: Low Serum Mg and Risk Of Developing Severe Covid-19 In Hospi...mentioning
confidence: 99%